2023
DOI: 10.1038/s41467-023-38336-5
|View full text |Cite
|
Sign up to set email alerts
|

Selective conversion of CO2 to isobutane-enriched C4 alkanes over InZrOx-Beta composite catalyst

Abstract: Direct conversion of CO2 to a single specific hydrocarbon with high selectivity is extremely attractive but very challenging. Herein, by employing an InZrOx-Beta composite catalyst in the CO2 hydrogenation, a high selectivity of 53.4% to butane is achieved in hydrocarbons (CO free) under 315 °C and 3.0 MPa, at a CO2 conversion of 20.4%. Various characterizations and DFT calculation reveal that the generation of methanol-related intermediates by CO2 hydrogenation is closely related to the surface oxygen vacanci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 62 publications
2
13
0
Order By: Relevance
“…All of the NMR experiments were carried out on a Bruker AVANCE-III 500 MHz spectrometer (11.7 T) operating at a Larmor frequency of 130.4 and 99.4 MHz for the 27 Al and 29 Si nuclei, respectively. A 4 mm MAS NMR probe was used to approach the 27 Al and 29 Si single-pulse experiments.…”
Section: T H Imentioning
confidence: 99%
See 3 more Smart Citations
“…All of the NMR experiments were carried out on a Bruker AVANCE-III 500 MHz spectrometer (11.7 T) operating at a Larmor frequency of 130.4 and 99.4 MHz for the 27 Al and 29 Si nuclei, respectively. A 4 mm MAS NMR probe was used to approach the 27 Al and 29 Si single-pulse experiments.…”
Section: T H Imentioning
confidence: 99%
“…All of the NMR experiments were carried out on a Bruker AVANCE-III 500 MHz spectrometer (11.7 T) operating at a Larmor frequency of 130.4 and 99.4 MHz for the 27 Al and 29 Si nuclei, respectively. A 4 mm MAS NMR probe was used to approach the 27 Al and 29 Si single-pulse experiments. The 27 Al MAS NMR spectra were recorded by using a single-pulse sequence with a pulse length of 0.26 μs (π/12) and a recycle delay of 1 s. Chemical shifts were referenced to those of (NH 4 )Al(SO 4 ) 2 •12H 2 O at −0.4 ppm.…”
Section: T H Imentioning
confidence: 99%
See 2 more Smart Citations
“…Although the tandem CO 2 hydrogenation over an OX-ZEO catalyst can acquire a relatively narrowed spectrum of hydrocarbon products with high selectivity, it is still rather challenging to get a specific hydrocarbon. Nonetheless, through selecting a proper framework of the zeotype moiety and elaborately regulating its acidity (including the strength, density, and location of acid sites) and morphology as well as combining with a matching oxide moiety, a variety of hydrocarbon products, such as ethene, propane, and butane, can be obtained with very high selectivity. Wang and co-workers observed that owing to the synergy between Cr 2 O 3 and H-ZSM-5, a selectivity of about 76% to aromatics was obtained for the CO 2 hydrogenation over the Cr 2 O 3 /H-ZSM-5 composite catalyst at a CO 2 conversion of 34.5% . Moreover, the fraction of benzene, toluene, and xylene (BTX) in aromatics could be greatly elevated through using a modified Cr 2 O 3 /H-ZSM-5@S-1 catalyst, where the neutralization of acid sites at the outer surface of H-ZSM-5 by S-1 (silicalite-1) on the core–shell structured H-ZSM-5@S-1 could precisely suppress the isomerization and other side reactions.…”
Section: Introductionmentioning
confidence: 99%